1998
DOI: 10.1042/bj3310465
|View full text |Cite
|
Sign up to set email alerts
|

The negative charge of glutamic acid-820 in the gastric H+,K+-ATPase α-subunit is essential for K+ activation of the enzyme activity

Abstract: To investigate the role of Glu820, located in transmembrane domain M6 of the alpha-subunit of gastric H+,K+-ATPase, a number of mutants was prepared and expressed in Sf9 cells using a baculovirus encoding for both H+,K+-ATPase subunits. The wild-type enzyme and the E820D (Glu820-->Asp) mutant showed a similar biphasic activation by K+ on the ATPase activity (maximum at 1 mM). The mutant E820A had a markedly decreased K+ affinity (maximum at 40-100 mM). The other mutants, E820Q, E820N, E820L and E820K, showed n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…is involved in determining the affinity for K ϩ in the K ϩ -ATPase activity (7,8) and its dephosphorylation step as shown in the present study. The negative charge of this glutamic acid was ably recovered at 10°C.…”
Section: Discussionmentioning
confidence: 87%
“…is involved in determining the affinity for K ϩ in the K ϩ -ATPase activity (7,8) and its dephosphorylation step as shown in the present study. The negative charge of this glutamic acid was ably recovered at 10°C.…”
Section: Discussionmentioning
confidence: 87%
“…ATP-dependent Phosphorylation-ATP-dependent phosphorylation was determined as described previously (37,38,42). Sf9 membranes (1-6 g) were incubated at 0 or 21°C in 50 mM Hepes-Tris (pH 6.0) containing 1.3 mM MgCl 2 and other ions and drugs as indicated in a volume of 80 l. After 30 -60 min, 20 l of 0.5 M [␥-32 P]ATP was added, and the mixture was incubated for 10 s at the same temperature as before.…”
Section: Methodsmentioning
confidence: 99%
“…This difference is due to the much faster rate of the E 2 K 3 E 1 K conversion in the latter enzyme (6,38). It has been shown that four negatively charged residues present in transmembrane segments 4 -6 play a role in cation-activated reactions of both ATPases (7)(8)(9)(10)(11)(12)(13). With the exception of a single residue in M6…”
mentioning
confidence: 99%